Interferensi Gramatikal Bahasa Indonesia dalam MahÄrah KalÄm Santriwati KMI Pondok Modern Ar-Risalah Ponorogo - Ni'mah, Jauharotun (IAIN Salatiga, 2018)
Language plays an important role in human life. language and humans can not be separated. Humans in all their activities need language to communicate with other humans. Communication has various kinds, one of which is oral communication that can cause interference. This research is descriptive in qualitative form. In this study the author uses listening method, the basic technique is